2007
DOI: 10.1007/s10517-007-0239-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ATP and its analogs on contractility of rat myocardium during ontogeny

Abstract: The effects of P2-receptor agonists on myocardial contractility were examined in rats aging 14-100 days. ATP and its stable analog 2-methylthio-ATP potentiated the contraction force of isolated myocardial strips in a dose-dependent manner. The agonist concentrations producing the positive inotropic effect increased from days 14 to 100 of life. The efficiency of extracellular purines depends on animal age: in 14- and 56-day rats the positive inotropic effects of ATP and 2-methylthio-ATP were similar, while in 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…The inhibitory effects produced by ATP and β-NAD were weakly age-dependent and were almost similar at all studied stages of postnatal ontogenesis in all types of myocardial preparations except adult ventricular myocardium. Several studies showed that extracellular ATP affects cardiac function in juvenile and adult mammals via purine P1 and P2 receptors [23]. Here, we show that β-NAD induces direct postsynaptic nerve-independent cardiac effects in early postnatal life similarly to ATP.…”
Section: Age-specific Effects Of Atp and β-Nad In The Rat Heartsupporting
confidence: 50%
“…The inhibitory effects produced by ATP and β-NAD were weakly age-dependent and were almost similar at all studied stages of postnatal ontogenesis in all types of myocardial preparations except adult ventricular myocardium. Several studies showed that extracellular ATP affects cardiac function in juvenile and adult mammals via purine P1 and P2 receptors [23]. Here, we show that β-NAD induces direct postsynaptic nerve-independent cardiac effects in early postnatal life similarly to ATP.…”
Section: Age-specific Effects Of Atp and β-Nad In The Rat Heartsupporting
confidence: 50%
“…ATP was detected only in pear fruits, and its level was decreased by FD, just as demonstrated in their report. ATP is an unstable metabolite, which is rapidly hydrolyzed to ADP and phosphate 47, 48. Minute effects of FD on cellular structure may lead the hydrolysis of ATP.…”
Section: Discussionmentioning
confidence: 99%